2012
DOI: 10.1002/ijc.27482
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram, an old drug with new potential therapeutic uses for human hematological malignancies

Abstract: Disulfiram (DSF) is an aldehyde dehydrogenase inhibitor currently used for the treatment of alcoholism. Here, we show that multiple myeloma (MM) cell lines and primary cells from newly diagnosed and relapsed/resistant patients affected by MM, acute myeloid and lymphoblastic leukemia are significantly sensitive to DSF alone and in combination with copper. These effects are present at doses lower than those achievable in vivo after DSF standard administration. The cytotoxic effect achieved by this treatment is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 28 publications
0
58
1
Order By: Relevance
“…Recently, several independent groups, including this study, have identified DSF through high-throughput screens as a potential therapeutic for the treatment of various cancers including glioblastoma (14)(15)(16)(17)(18)(19). As DSF has been used clinically for over 60 years to treat alcoholism, its pharmacokinetics has been extensively studied and shown to have an excellent safety record at FDArecommended doses (20,21).…”
Section: Introductionmentioning
confidence: 98%
“…Recently, several independent groups, including this study, have identified DSF through high-throughput screens as a potential therapeutic for the treatment of various cancers including glioblastoma (14)(15)(16)(17)(18)(19). As DSF has been used clinically for over 60 years to treat alcoholism, its pharmacokinetics has been extensively studied and shown to have an excellent safety record at FDArecommended doses (20,21).…”
Section: Introductionmentioning
confidence: 98%
“…15,16 Oral DSF as a cancer therapeutic has been tested in several completed and on-going trials (ClinicalTrials.gov Identifier NCT00256230, NCT00742911, NCT01118741), but no positive outcomes have been reported. The poor results following oral administration of DSF are due to its extreme instability A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 5 under physiological conditions; DSF is quickly degraded in the gastrointestinal system, during the hepatic first-pass effect and in the blood stream. 17,18 As a result, orally administered DSF does not reach tumor tissues at therapeutic concentrations, which is a major limitation for the clinical usage of DSF in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…4 In recent years, researchers have discovered that DSF and its metabolites may have antitumor and chemosensitizing activities, possibly through inhibition of proteasome activity. [5][6][7][8] In fact, high-throughput screening has identified DSF as a potential therapeutic for triple-negative breast cancer cells, breast cancer stem cells and human glioblastoma stem cells by modulating ROS-MAPK and NFκB pathways. 9-12 DSF also permanently inactivates the human multidrug resistance p-glycoprotein and has been approved for prevention of related cases of drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Disulfiram (DS), a member of dithiocarbamate family with 297 Da molecular weight, is oral aldehyde dehydrogenase (ALDH) inhibitor that has been used in the treatment of alcoholism since 1940s [13]. During the last few years, a growing body of evidence from both in vivo and in vitro studies indicated that disulfiram has anticancer properties [2].…”
Section: Introductionmentioning
confidence: 99%